Family Models in Europe in the Context of Women's Status - Magdalena Muszynska (Hungarian Demographic Research Institute, 2004)
This paper attempts to identify relations between family models existing in Europe with the status of woman in the respective societies. It discusses not only the actual roles played by women in the society but also public opinion regarding which of the mare appropriate. Utilising the theory of Becker (Becker 1981) and a set of contingency hypotheses (Liefbroer-Corijn 1999), the paper shows that different models of family are associated with different degrees of intensity incultural and structural tensions.
Keywords: 300; Armut; Risiko; Haushaltseinkommen; Bevölkerungsstruktur; Ungarn; Soziale Ungleichheit